Intellectual Repercussions of the Council of Florence - Ševčenko, Ihor (Church history, 1955)
At Ferrara and Florence, Western intellectuals met with the greatest Greek scholarly and theological delegation that ever came to Latin soil. The Greeks did not come empty-handed. They brought with them de luxe editions of Greek sacred and, above all, secular authors—coveted treasures for Renaissance Italians. To judge by the letters in which Ambrogio Traversari announced the arrival of the Greeks, Christian Humanists were as much interested in the codices of Plato, Plutarch, Euclid and Ptolemy, brought by the Emperor and Bessarion, as in the cause which brought the Greeks to Italy.